Developing a Learner-Centered International Class Model for Institutional Globalization: Multi-Site Evidence from Indonesian Universities - Hamka Hamka; Imam Nur Aziz (LP. Ma'arif Janggan Magetan, 2024)
This study addresses the persistent gap in empirically grounded, learner-centered models for international classes within Indonesian higher education, amid intensifying globalization demands. Despite policy pushes like Merdeka Belajar-Kampus Merdeka, prior research remains fragmented, overlooking integrated analyses of learning conditions, methods, and outcomes. Employing a qualitative multi-site design, we gathered data via classroom observations, semi-structured interviews, and document reviews from March to August 2023 across eight leading universities Airlangga, Gadjah Mada, Indonesia, and others involving 25 students, 8 lecturers, and program heads per site (total 200+ participants). Analysis followed Miles et al.'s interactive model (data reduction, display, verification) with triangulation for credibility. Findings indicate international classes foster diversity in nationality, socioeconomic backgrounds, ethnicity, cultural interactions, and academic mobility, while outperforming regular classes in facilities, English proficiency, student performance, and outcomes—yet reveal inconsistencies in consistent language use (70% Bahasa Indonesia-dominant) and innovative pedagogy (65% lecture-based). Participants view these practices as feasible and aligned with institutional goals. We propose a pioneering structured model integrating conditions (e.g., objectives, constraints), methods (collaborative, reflective), and outcomes (global competence), tailored for Indonesia. This framework advances fragmented studies, offering actionable strategies for universities to enhance competitiveness via MBKM and internationalization.